The prodigal son in English and American literature: five hundred years of literary homecomings - Jack, Alison M. (Biblical Refigurations Ser., 2019)
This groundbreaking study focuses on the reconfiguring of the character of the Prodigal Son and his family as they appear in drama, novels, and poetry in English from the fifteenth to the twenty-first centuries.